Keefektifan Grup Whatsapp Dalam Pembentukan Community Of Inquiry (CoI) Melalui Blended Learning Pada Materi Penyetaraan Reaksi - Mohammad Alex Firdaus; Najmah Najmah; Haris Munandar (Jurnal Ilmiah Kanderang Tingang, 2023)
The aim of this study was to know the effectiveness of WhatsApp group in creating Community of Inquiry (CoI) through blended learning in Balancing Chemical Equations. The object research was 30 students of 1 Giri senior High School. The research method used was descriptive qualitative. The success rate of CoI through blended learning can be seen from the relationship of the three elements of the CoI framework: social relations, appropriate teaching methods, and cognitive aspect. The social relations of this study were characterized by the variety of learning resources used by students in discussion forums in WhatsApp group, either of textbooks, videos, or sources from the internet. This was because students felt comfortable as evidenced by the quantity of interaction among students and the interaction of students with educators in discussion forums. The success of the teaching element was observed from the process of providing facilities and guidance. The facility for establishing CoI through blended learning in this study was accommodated by the WhatsApp group. While the guidance carried out by educators is done by explaining the learning flow and directing students to actively interact and provide reinforcement for answers. The success of the cognitive aspect was obtained from the passage of all stages of CoI in constructing the Balancing Chemical Equations material. In this study, it was known that the exploration and integration stages dominate more than the other steps. This indicated that students were able to focus themselves on questions posed by other students related to teaching materials by seeking information through various sources.